Metabolite regulation of the mitochondrial calcium uniporter channel. (December 2020) - Tomar, Dhanendra; Elrod, John W.
Graphical abstract: Abstract: Calcium (Ca 2+ ) is known to stimulate mitochondrial bioenergetics through the modulation of TCA cycle dehydrogenases and electron transport chain (ETC) complexes. This is hypothesized to be an essential pathway of energetic control to meet cellular ATP demand. While regulatory mechanisms of mitochondrial calcium uptake have been reported, it remains unknown if metabolite flux itself feedsback to regulate mitochondrial calcium (m Ca 2+ ) uptake. This hypothesis was recently tested by Nemani et al. ( Sci. Signal. 2020) where the authors report that TCA cycle substrate flux regulates the mitochondrial calcium uniporter channel gatekeeper, mitochondrial calcium uptake 1 (MICU1), gene transcription in an early growth response protein 1 (EGR1) dependent fashion. They posit this is a regulatory feedback mechanism to control ionic homeostasis and mitochondrial bioenergetics with changing fuel availability. Here, we provide a historical overview of mitochondrial calcium exchange and comprehensive appraisal of these results in the context of recent literature and discuss possible regulatory pathways of m Ca 2+ uptake and mitochondrial bioenergetics.